CtrA activates the expression of glutathione S-transferase conferring oxidative stress resistance to Ehrlichia chaffeensis - Liang, Qi’an; Yan, Jiaqi; Zhang, Shuwen; Yang, Nan; Li, Meifang; Jin, Yongxin; Bai, Fang; Wu, Weihui; Cheng, Zhihui (Frontiers in Cellular and Infection Microbiology, 2022)
Ehrlichia chaffeensis, the causative agent of human monocytic ehrlichiosis (HME), is a Gram-negative obligatory intracellular bacterium, which infects and multiplies in human monocytes and macrophages. Host immune cells produce reactive oxygen species (ROS) to eliminate E. chaffeensis upon infection. E. chaffeensis global transcriptional regulator CtrA activates the expression of GshA and GshB to synthesize glutathione (GSH), the most potent natural antioxidant, upon oxidative stress to combat ROS damage. However, the mechanisms exploited by E. chaffeensis to utilize GSH are still unknown. Here, we found that in E. chaffeensis CtrA activated the expression of glutathione S-transferase (GST) upon oxidative stress, and E. chaffeensis GST utilizes GSH to eliminate ROS and confers the oxidative stress resistance to E. chaffeensis. We found that CtrA bound to the promoter regions of 211 genes, including gst, in E. chaffeensis using chromatin immunoprecipitation coupled to deep sequencing (ChIP-seq). Recombinant E. chaffeensis CtrA directly bound to the gst promoter region determined with electrophoretic mobility shift assay (EMSA), and activated the gst expression determined with reporter assay. Recombinant GST showed GSH conjugation activity towards its typical substrate 2,4-dinitrochlorobenzene (CDNB) in vitro and peptide nucleic acid (PNA) transfection of E. chaffeensis, which can knock down the gst transcription level, reduced bacterial survival upon oxidative stress. Our results demonstrate that E. chaffeensis CtrA regulates GSH utilization, which plays a critical role in resistance to oxidative stress, and aid in the development of new therapeutics for HME.